FACTORS AFFECTING INFORMATION UTILIZATION IN COFFEE PRODUCTION PACKAGES AMONG SMALLHOLDER FARMERS IN WEST ETHIOPIA - Alemu Mulatu Gutama; Guta Regasa Megerssa; Akalu Dafisa Sima (Socio-Economics/Agribusiness Department, 2019)
the main objectives of the study was intended to investigate factor affecting coffee production packages information utilization by smallholder coffee growers in Ethiopia. Cross sectional research design and two stages sampling technique was used to select sample households. The data were collected from both primary and secondary sources. The data was analyzed using descriptive and inferential statistics to describe factors affecting information utilizations in coffee production packages. Ordered logistic regression model was used to analyze the factors affecting information utilization in coffee package. From 16 explanatory variables hypothesized: age, household size, on-farm income, coffee farm size, radio use, social participation, farmer’s willingness to share information and farmers perception toward coffee package practice were found to be significant at less than 1% and 5% significance level. In a nutshell, there are different demographic, economic, institutional and psychological factors which result in the reduction of coffee yields. Therefore, rural development strategy should give priority attention to promote coffee production package technologies by providing sustainable technical services through training practically by introducing coffee demonstration site and managing the existing old coffee farm in the study area.